Addition of nintedanib or placebo to neoadjuvant gemcitabine and cisplatin in locally advanced muscle-invasive bladder cancer (NEOBLADE): a double-blind, randomised, phase 2 trial. Issue 5 (May 2022) - Hussain, Syed A; Lester, Jason F; Jackson, Richard; Gornall, Matthew; Qureshi, Muneeb; Elliott, Anthony; Crabb, Simon J; Huddart, Robert A; Vasudev, Naveen; Birtle, Alison J; Worlding, Jane; James, Nicholas D; et al.
Summary: Background: Recurrence is common after neoadjuvant chemotherapy and radical treatment for muscle-invasive bladder cancer. We investigated the effect of adding nintedanib to neoadjuvant chemotherapy on response and survival in muscle-invasive bladder cancer. Methods: NEOBLADE was a parallel-arm, double-blind, randomised, placebo-controlled, phase 2 trial of neoadjuvant gemcitabine and cisplatin chemotherapy with nintedanib or placebo in locally advanced muscle-invasive bladder cancer. Patients aged 18 years or older, with an Eastern Cooperative Oncology Group performance status of 0–1, were recruited from 15 hospitals in the UK. Patients were randomly assigned (1:1) to nintedanib or placebo using permuted blocks with random block sizes of two or four, stratified by centre and glomerular filtration rate. Treatments were allocated using an interactive web-based system, and patients and investigators were masked to treatment allocation throughout the study. Patients received oral nintedanib (150 mg or 200 mg twice daily for 12 weeks) or placebo, in addition to usual neoadjuvant chemotherapy with intravenous gemcitabine 1000 mg/m 2 on days 1 and 8 and intravenous cisplatin 70 mg/m 2 on day 1 of a 3-weekly cycle. The primary endpoint was pathological complete response rate, assessed at cystectomy or at day 8 of cyclde 3 (plus or minus 7 days) if cystectomy did not occur. Primary analyses were done in the intention-to-treat population. The trial is registered with EudraCT, 2012-004895-01, and ISRCTN, 56349930, and has completed planned recruitment. Findings: Between Dec 4, 2014, and Sept 3, 2018, 120 patients were recruited and were randomly allocated to receive nintedanib (n=57) or placebo (n=63). The median follow-up for the study was 33·5 months (IQR 14·0–44·0). Pathological complete response in the intention-to-treat population was reached in 21 (37%) of 57 patients in the nintedanib group and 20 (32%) of 63 in the placebo group (odds ratio [OR] 1·25, 70% CI 0·84–1·87; p=0·28). Grade 3 or worse toxicities were observed in 53 (93%) of 57 participants who received nintedanib and 50 (79%) of 63 patients in the placebo group (OR 1·65, 95% CI 0·74–3·65; p=0·24). The most common grade 3 or worse adverse events were thromboembolic events (17 [30%] of 57 patients in the nintedanib group vs 13 [21%] of 63 patients in the placebo group [OR 1·63, 95% CI 0·71–3·76; p=0·29]) and decreased neutrophil count (22 [39%] in the nintedanib group vs seven [11%] in the placebo group [5·03, 1·95–13·00; p=0·0006]). 45 treatment-related serious adverse events occurred in the nintedanib group and 43 occurred in the placebo group. One treatment-related death occurred in the placebo group, which was due to myocardial infarction. Interpretation: The addition of nintedanib to chemotherapy was safe but did not improve the rate of pathological complete response in muscle-invasive bladder cancer. Funding: Boehringer Ingelheim.